FEM modelling of lumbar vertebra system / Stuburo juosmens slankstelių sistemos skaitinis tyrimas BEM - Rimantas Kačianauskas (Mokslas: Lietuvos Ateitis, 2013)
The article presents modeling of human lumbar vertebra and it‘sdeformation analysis using finite elements method. The problemof tissue degradation is raised. Using the computer aided modelingwith SolidWorks software the models of lumbar vertebra(L1) and vertebra system L1-L4 were created. The article containssocial and medical problem analysis, description of modelingmethods and the results of deformation test for one vertebramodel and for model of 4 vertebras (L1-L4).